From the Eye to the Heart: Association between Age-Related Macular Degeneration and Cardiovascular Disease (a Systematic Review): Oral Presentation - Observational Study - General practitioner - Sausan; Presialia, Athira; Khalifah, Rasyad; Adriono, Gitalisa Andayani (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesAge-related macular degeneration (AMD) is the third leading cause of global blindness, whilecardiovascular disease (CVD) is recognized as a major cause of morbidity and mortality. Both arecomplex diseases associated with aging. It has recently been argued that there is an associationbetween AMD and CVD. This study examined whether AMD increased the risk of CVD and/ or CVDmortality. MethodsA systematic review was conducted through three databases (Pubmed, Scopus, and Embase) forrelevant studies published between 2016-2023. We selected studies which focused on subjects withAMD, regardless of stages, and their risks for developing CVD and/or CVD mortality. ResultsTwo cohort studies and one case-control study are included, involving 93.388 patients aged >40years old. One cohort study found that subjects with choroidal neovascularization were associatedwith an increased rate of cardiovascular mortality (HR 3.16 95% CI 1.62-6.15). Another study alsofound that AMD was associated with a 1.58 fold increased risk of heart failure (adjusted OR, 1.56;95% CI, 1.16–1.87; P<0.001) after adjustment for confounders. Moreover, aside from the variableson which this systematic review focused on, the cohort studies also found AMD correlation withother diseases and causes of mortality. ConclusionIndividuals with AMD have higher risk for developing CVD. Thus, screening for AMD may bebeneficial in preventing CVD.